1997
DOI: 10.1126/science.278.5344.1752
|View full text |Cite
|
Sign up to set email alerts
|

The Mars Pathfinder Atmospheric Structure Investigation/Meteorology (ASI/MET) Experiment

Abstract: close to the observed value 29sin(ᐉ ϩ 241°) mas. 23. We thank the Mars Pathfinder project team for their enthusiasm and assistance in acquiring and understanding the tracking measurements; R. Wimberly for recovery of the Viking lander Doppler data; and J. Williams and an anonymous referee for helpful suggestions. The research described in this paper was carried out by the Jet Propulsion Laboratory, Califor- The Mars Pathfinder atmospheric structure investigation/meteorology (ASI/MET ) experiment measured the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
325
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 424 publications
(355 citation statements)
references
References 24 publications
26
325
1
3
Order By: Relevance
“…The deepest pressure drops are predicted at the edges of convective cells (where strongest updrafts occur) and correspond to convective vortices (Michaels and Rafkin, 2004) which could form dust devils should surface dust be available to be lifted. Pressure drops associated with dust devils have been observed both on Earth (Renno et al, 2004;Lorenz, 2012) and Mars (Schofield et al, 1997;Ellehoj et al, 2010). In fact, the method by Lorenz (2012) is able to capture all convective vortices rather than only dust devils (i.e.…”
Section: Discussionmentioning
confidence: 93%
“…The deepest pressure drops are predicted at the edges of convective cells (where strongest updrafts occur) and correspond to convective vortices (Michaels and Rafkin, 2004) which could form dust devils should surface dust be available to be lifted. Pressure drops associated with dust devils have been observed both on Earth (Renno et al, 2004;Lorenz, 2012) and Mars (Schofield et al, 1997;Ellehoj et al, 2010). In fact, the method by Lorenz (2012) is able to capture all convective vortices rather than only dust devils (i.e.…”
Section: Discussionmentioning
confidence: 93%
“…Much like the observations of Martian dust devils by Viking [Ryan and Lucich, 1983], these terrestrial dust devils are found to possess ''hot cores'' with temperatures steadily rising and ultimately peaking in the dust devil center (Figure 6c). As with the Mars Pathfinder meteorology results [Schofield et al, 1997;Murphy and Nelli, 2002], a small but detectable pressure decrease (1-2 mb) occurs in the dust devil center. The observations of thermal and pressure gradients suggest the dust devil is a miniconvective system, with fluid cyclonic motion (winds) ultimately driven by near-ground thermal energy.…”
Section: Arizona 2001: Truck Observationsmentioning
confidence: 99%
“…[4] Tracks left by the passage of dust devils are found on nearly every region across the Martian surface [Cantor and Edgett, 2002], and nearly every orbiter and lander sent from Earth has directly observed active plumes, including: Viking Landers 1 & 2 (passage of vortex cores inferred by meteorological data) [Ringrose et al, 2003], Viking Orbiters 1 & 2 [Thomas and Gierasch, 1985], Mars Pathfinder Lander [Schofield et al, 1997;Metzger et al, 1999] and Mars Global Surveyor (MGS) [Edgett and Malin, 2000]. Measured diameters were between 28-509 m, with heights of 170 -8500 m. An extensive survey using 2 p.m. Mars Orbiter Camera (MOC) wide and narrow-angle images was conducted by Fisher et al [2005], who determined that Martian dust devils exhibit some regional and seasonal dependence with a bias toward northern latitudes during the warmest seasons.…”
Section: Introductionmentioning
confidence: 99%